TYPES OF ATTACKS ON WEBSITES AND METHODS OF THEIR PREVENTION (Web of Technology: Multidimensional Research Journal, 2025)
This article discusses various types of attacks on websites. The most common types of cyberattacks observed today and the causes of such attacks are analyzed. Information is provided on major attacks such as Distributed Denial of Service (DDoS), SQL injection, Man-in-the-Middle attacks, Cross-Site Scripting (XSS), and DNS attacks. In addition, the causes of attacks on websites and recommendations for their prevention are presented.